EVALUATION OF THE IMPLEMENTATION OF THE EXTRACURICULAR SCOUTING PROGRAM - Hani Arie RACHMANIE; Ihsana El Khuluqo; Istaryatiningtias ISTARYATININGTIAS (Journal of Education and Leadership in Education, 2022)
The evaluation research on the implementation of extracurricular programs aims to describe the results of research on how the program's achievements from the implementation of the mandatory Scout extracurricular activities. The research in this thesis is motivated by the condition of the lack of efficiency in the mandatory Scout extracurricular activities, and the role of teachers in motivating activities in the implementation of activities that take place every week is felt to be less than optimal and efficient. This study uses qualitative research methods with descriptive research type. The location of this research includes research instruments of parties who have activities in schools, especially students as the main object in the implementation of the mandatory Scout extracurricular activity program as recommended by the Government. Determination of information is done by purposive sampling technique. Meanwhile, the data collection technique was carried out by observation, in-depth interviews with informants, taking documentation as data, and research using triangulation techniques, which included standard utility. Furthermore, the data analysis technique is by means of data reduction, data presentation, methods, discussions with colleagues and drawing conclusions. The results obtained from this study indicate that the process of implementing the program "Evaluation of the Implementation of Scout Extracurricular Programs at MI Al-Khairiyah Pagi Mampang Prapatan, South Jakarta" is less effective and needs improvement and improvement in the implementation of the mandatory Scout extracurricular activity program.